The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/min11030242
|View full text |Cite
|
Sign up to set email alerts
|

Contamination Alters the Physicochemical and Textural Characteristics of Clays in the Sediments of the Peri Urban Reconquista River, Affecting the Associated Indigenous Microorganisms

Abstract: The physicochemical and textural characteristics of river sediments and, essentially, their clays, are at the center of a network of biological and geochemical factors that are mutually modifying. Therefore, the contamination, the characteristics of the clays, and the associated microorganisms strongly influence each other. In this work, sediments from two sites of the urban Reconquista River, near Buenos Aires City, Argentina, exposed to different environmental contexts were characterized. The huge difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Prolonged exposure of streambed sediments to the contaminants could eventually alter the chemical properties of the sediments [170]. For instance, in Oak Ridge, USA, after the historical industrial releases of mercury (Hg) in the East Fork Poplar Creek, a study has found evidences of geochemical transformation of sediments into Hg-bound sediments and degradation of in-stream environment [171].…”
Section: Biochemical Impactsmentioning
confidence: 99%
“…Prolonged exposure of streambed sediments to the contaminants could eventually alter the chemical properties of the sediments [170]. For instance, in Oak Ridge, USA, after the historical industrial releases of mercury (Hg) in the East Fork Poplar Creek, a study has found evidences of geochemical transformation of sediments into Hg-bound sediments and degradation of in-stream environment [171].…”
Section: Biochemical Impactsmentioning
confidence: 99%
“…Under the low redox potential of the rivers water, heavy metals are precipitated or adsorbed on different mineral components of the sediment, turning it into a heavy metal reservoir (Porzionato et al, 2013). A thorough characterization of the rivers water and sediment was previously performed by our group (Tufo et al, 2018(Tufo et al, , 2021. The Reconquista river has high levels of chromium, among other diverse pollutants, and being the second most polluted river in Argentina it represents an acute environmental problem (Porzionato et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It has thus become a typical example of the adverse impact of human activities on the health of aquatic environment (Salibia ´n, 2006). Previous studies (Nader, 2015;Ossana et al, 2013Ossana et al, , 2016Rigacci et al, 2013;Tufo et al, 2021;and references therein) have determined that trace elements such as chromium (Cr), cadmium (Cd), lead (Pb), copper (Cu), zinc (Zn) and arsenic (As) are the main pollutants in the water of the Reconquista River. The introduction of these trace elements is a consequence of the waste of fossil fuel combustion, leakage of metal-containing motor oils and untreated sewage discharged by electroplating, electrical, paint, food, tannery, chemistry and nonferrous smelting industries (Mondino, 2007;Pescuma & Guaresmi, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Many authors have studied their toxicological impacts on the biota (Herkovits et al, 1996;Loez & Topalia ´n, 1999;Ossana et al, 2013Ossana et al, , 2016Rigacci et al, 2013). Of note, heavy metals retained in sediment particles (Cantera et al, 2018;Tufo et al, 2021) may eventually be released to water and generate adverse effects in exposed animals and humans (e.g., Ferraro et al, 2012).…”
Section: Introductionmentioning
confidence: 99%